(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Terminalia catappa family combretaceae moreover known as Indian almond was a large, spreading tree scattered throughout the tropics in coastal environments in India. Anti-ulcer activity of ethanolic extract of T. catappa (250 and 500 mg/kg b.w) was examined on pyrolic ligated induced ulcer model in rats. Omeprazole was used as standard. The anti-ulcer activity of T. catappa was evaluated with the help of ulcer index and histopathological examination. Preliminary phytochemical screening and acute toxicity studies of T. catappa also carried out. The extract showed significant (p < 0.001) reduction in pH, gastric volume, free acidity, total acidity and ulcer index in dose dependent manner as compared to control. The extract did not produce any toxic effects even at high doses. The anti-ulcer activity was probably due to the presence of flavonoids.